The Economics of Soil Fertility Management in Malawi - Sauer, Johannes; Tchale, Hardwick (2012)
We estimated a normalized translog yield-response model using African farm-household survey data to compare the yield of smallholder maize production under integrated soil fertility management (ISFM) and chemical-based soil fertility management. Controlling for other factors, maize yield responses were higher under ISFM. Results suggest ISFM practices would significantly improve the profitability of smallholder maize production, especially under escalating fertilizer prices.